Side table from oil palm lumber / Muhammad Arbain Mat Yuti and Nik Hazlan Nik Hashim - Mat Yuti, Muhammad Arbain; Nik Hashim, Nik Hazlan (2014)
This research was conducted to examine the feedback from people about the important of oil palm lumber in furniture making. The new material of product is the major for this study. The table was produced, and the data was collected by survey from questionnaires. The questionnaires were too distributed to 90 correspondences from students and staff of UITM Pahang and also the publics. Then, the data were analyses by SPSS to get the results. Most of the correspondences given the positive feedback regarding on the new material used suitable for simple design furniture, easy to handle, portable, saving space, light attractive. Overall table by using oil palm lumber were accepted by all correspondences in range of age, gender and position.